Study of Safe Separation Distances between Rural Wells and Neighbouring Soak-Away Systems - OGEDENGBE, O. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2020)
It is becoming increasingly common for educated Nigerians to build houses in rural and semi-urban areas of the country. The plan of a typical modern house includes construction of a septic tank and soakaway for disposal of wastewaters. Very often, a well is dug on the same plot of land for supply of water in lieu of tap water supply. The study reported in this paper shows that in a silty sand soil, the safe separation is about 14 meters,